Utilization of Natural Milk Coagulant in The Processing of Indigenous Dairy Product (Palopo) - Agil, Alwi; Bulkaini, Bulkaini; Wulandani, Baiq Rani Dewi; Kisworo, Djoko; Fahrullah, Fahrullah (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
The objective of this study is to ascertain the impact of employing natural coagulants, namely eggplant para (Solanum indicum), biduri sap (Calotropis gigantea), and papaya sap (Carica papaya L.), on the chemical properties, antioxidant levels, and organoleptic properties of palopo. The present study employed a Completely Randomized Design (CRD), utilizing three natural coagulant treatments (eggplant, biduri sap, and papaya sap) each at 0.2% of the sample weight, with five replicates. The research variables encompassed pH, water content, ash, crude protein, crude fat (utilizing the proximate analysis method), antioxidant content (employing the DPPH method), and organoleptic values (aroma, taste, colour, texture, and overall acceptance) (using the hedonic method). The findings indicated that the type of coagulant employed exerted a highly significant effect (P<0.01) on the water content, protein and antioxidant levels of palopo, while no significant effect (P>0.05) was observed on pH, fat content, and ash content. The utilization of eggplant (Solanum indicum) as a natural coagulant resulted in a high level of protein in palopo (7.33%), while the application of papaya latex (Carica papaya L.) led to a higher level of antioxidants in palopo (80.05%) compared to other types of coagulants. The incorporation of natural coagulant eggplant parboil can yield palopo that is particularly prized for its optimal texture and palatability. Conclusion: The incorporation of natural coagulant Eggplant (Solanum indicum) in the manufacturing process of palopo ensures optimal chemical quality and acceptance, while papaya latex (Carica papaya L.) contributes the highest antioxidant content, thereby possessing the potential to enhance the functional value of the product.